Analisis Kesalahan Berbahasa dalam Penulisan Surat Undangan Organisasi Kemahasiswaan di Fakultas Ilmu Budaya Universitas Diponegoro - Mujid Farihul Amin; Suyanto Suyanto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Letter writing is a means of communication used to convey information from one party to another party. In writing a letter of invitation made by the student organization at the Faculty of Humanities, Diponegoro University speaking there are errors. Language errors can be classified in terms of spelling mistakes and grammatica lerrors from the corner. From the point of spelling mistakes, such as errors in writing on the letter head, dated letters, numbers, attachment, respect, and the contents of the letter. Errors of grammar corner there are two, namely the use of pronouns in the paragraph cover letter and there are still fragmentary sentences.